Chapter Disciplinamento sociale e teologia nei Quodlibeta di Pietro de Trabibus - TABARRONI, Andrea (Reti Medievali E-Book, 2020)
This article analyzes some questiones quodlibetales (1296-1297) delivered by Peter of Trabibus, a Florentine Franciscan of Santa Croce. He reflects on and attempts to regulate Florentine society in times of unprecedented political and economic dynamism. Dealing with the definition of "new" sins, these questions examine tantalizing cases pertaining to economic life outside the convent, and which thus constitute matters of great juridical and political interest. The critical edition of Petrus of Trabibus' questions 17 to 22, Quodlibet 2, here published for the first time, completes this contribution.